XRD AND IR INVESTIGATIONS OF SOME COMMERCIAL POLYSTYRENE SAMPLES THERMALLY DEGRADED - NICULĂESCU, Carmen; OLAR, Loredana; ȘTEFAN, Răzvan; TODICA, Mihai; POP, Cornel-Viorel (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Thermal degradation of commercial polystyrene was investigated by XRD and FT-IR methods. The samples were heated 30 minutes at temperatures 140ºC, 200ºC, 250ºC, 300ºC and 350ºC and then brought back to room temperature. XRD investigation denotes structural modification for samples heated above 200ºC. This modification is confirmed by FT-IR measurements. Some vibration bands are affected by thermal degradation at temperatures higher than 200ºC. Both FT-IR and XRD methods reveal modification of microscopic structure of the polystyrene submitted to thermal degradation.